Emerging roles of natural killer cell ligands—HLA-E, HLA-F, HLA-G, MICA, and MICB—in in vitro fertilization outcomes - Chaaithanya, Itta Krishna; Rajalingam, Raja (Frontiers in Genetics, 2025)
Infertility affects approximately one in six individuals globally and represents a complex public health concern influenced by a range of biological, environmental, and socioeconomic factors. In vitro fertilization (IVF) has emerged as a pivotal assisted reproductive technology (ART), yet its success is often hindered by recurrent implantation failure (RIF) and hypertensive complications such as preeclampsia (PE). Recent research highlights the critical role of the immune system particularly non-classical Human Leukocyte Antigen (HLA) class I molecules (HLA-G, HLA-E, HLA-F) and MHC class I chain-related proteins (MICA/B) in modulating maternal-fetal tolerance and determining IVF outcomes. This review synthesizes emerging evidence on the structure, expression, receptor interactions, and polymorphisms of these molecules, emphasizing their roles in embryo implantation, immune modulation, and pregnancy maintenance. Soluble HLA-G (sHLA-G) has shown promise as a biomarker for embryo viability, while variations in KIR–HLA interactions and polymorphisms in non-classical HLA genes have been linked to RIF and adverse reproductive outcomes. Despite promising findings, routine clinical testing of these markers remains limited due to methodological inconsistencies, lack of large-scale validation, and the multifactorial nature of implantation. Future research priorities include functional genomics, standardized diagnostic assays, AI-driven predictive tools, and translational trials of immunomodulatory therapies. Understanding the immunogenetic landscape offers new avenues for personalized reproductive care and improved IVF success rates.